Al iltifat in selected poems of Mahmood Darwish - Goodarzi, Fatemeh Lotfi (2013)
This study deals with one of the most important rhetoric terms which is “Iltifat” that represents one of the rhetoric styles: al-bayan, al-maani, al-badi’. This is due to its rhetoric uniqueness and its significance. This study looks at analyzing one of the rhetoric styles in Mahmood Darwish’s poetry. Darwish is one of the most popular modern Arabic poets in Palestine. Three of his collections of poems were selected and analysed. These three collections of poems which contain various types of Iltifat such as transformation among verb forms and syntactic structure, numbers and lexical formulas, were inductively analysed from various opinions in rhetoric, language, and syntax books or dictionaries. Two methods of analysis including inductive and analytic styles wereused to review the rhetoric approach for the purpose of figuring out the general and specific Iltifat indications among linguists and literary pioneers by pointing out the benefits of those opinions and the styles of applying the Iltifat methods in analyzing Darwish’s poetry namely the three collections selected for this study. The Iltifat in his poetry relies on one or two sentences or even three to ten sentences maximum regardless the number of lines. After that, types of Iltifat available in the three collections were categorized in a timetable showing the recurring patterns and the percentage of Iltifat in each collection. One of the most distinguished and interesting results is that some Iltifat types are used more than others. Transferring between various tools, for instance, was the most recurring type of Iltifat in the three collections whereas the transferring in numbers was less recurring pattern. Moreover, the study shed light on the benefits of Iltifat and its purposes like: veneration, exaggeration, reporting, rebuking, drawing attention, specifying and other secrets of rhetoric.